The placenta height. II quantitative ultrastructural study of placentas of Cerro de Pasco (height, 4,300 m.), Puno (height, 3,850 m.) And Lima (height, 150 m.) - Saldaña, Mario (2015)
It has conducted a quantitative study of electronic 3 placentas of Cerro de Pasco micrographs (height, 4,330 m.), 4 placentas of Puno (3,850 m.) And 4 placentas of Lima (150 m.). It has been determined that the area of the villous surface determined by light microscopy is increased due to the presence of microvillos by a factor of 5.23 in Cerro de Pasco, Puno 3.50 and 3.03 in Lima (mean values). As a result, the area of maternal-fetal exchange is of 60.72 m2 in Cerro de Pasco, Puno 38.92 m2 and 26.60 m2 in Lima. The finding is interpreted as an adaptive mechanism of the placenta in height to the situation of hypoxia, to favor the phenomena of maternal-fetal exchange. Simple linear measurements of the thickness of the placenta showed no difference between groups in height and sea level. Because of the relative character of the measurement is not discarded, real differences with other measurement. No differences were observed in the cytological composition and general ultrastructural features of maternal-fetal barrier height and sea level. However, the possibility is not ruled out differences in the number, shape and size of the cell organelles.